Photoinduced Changes in the Chlorophyll a to Chlorophyll b Ratio in Young Bean Plants - Argyroudi-Akoyunoglou, J. H. (1970)
An alternating light-dark system is described under which etiolated bean (Phaseolus vulgaris) leaves form selectively chlorophyll a. This system consists of cycles of 2 minutes of white light alternating with 98-minute dark periods. Etiolated tissue exposed to a series of such light-dark cycles accumulates chlorophyll a predominantly, with no lag phase in its biosynthesis. A very high ratio of chlorophyll a:chlorophyll b is thus established. The ratio increases with the number of light exposures up to about 45 such exposures and then it declines. Transfer of the etiolated tissue to continuous illumination after a number of such light exposures results in a dramatic drop of the chlorophyll a:chlorophyll b ratio to values normally found in green plants.